Design issues of optical IP routers for Internet backbone applications. - Callegati, F. (IEEE Communications magazine)
The rapid increase of Internet traffic is pushing the deployment of WDM technology in the next-generation high-speed Internet backbone. Routers in the backbone could still be the potential bottleneck. In this article we consider some design issues of high-throughput optical routers which combine the advantages of WDM with the new optical switching technology. We first introduce a proposed Internet architecture based on the optical burst switching mechanism. Some important design issues in optical buffering and control function are addressed which are expected to have significant effects on router performance. Numerical results of a simulation study are also presented along with discussions